2012
DOI: 10.2152/jmi.59.206
|View full text |Cite
|
Sign up to set email alerts
|

The effects measurement of hand massage by the autonomic activity and psychological indicators

Abstract: This study examined the effects of hand massage on autonomic activity, anxiety, relaxation and sense of affinity by performing it to healthy people before applying the technic in actual clinical practice. Findings were showed below: 1) the significant increase in the pNN50 and the significant decrease in the heart rate meant the intervention of massage increased the autonomic nervous activity, improved the parasympathetic nerve activity and reduced the sympathetic nerve activity. This means the subjects were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 7 publications
3
24
0
1
Order By: Relevance
“…Also, decreased sympathetic activity was indicated by decreased stress index and increased stress resistance. The results of this study were consistent with the previous studies [4], [10], [11], [19]. They found 20 minutes of light pressure of hand massage, a 30-minute session of TTM on to the back muscles, 80 minutes of touch massage (stroking) of the hands and feet, and a 5-minute hand holding could increase parasympathetic activity and decrease sympathetic activity, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, decreased sympathetic activity was indicated by decreased stress index and increased stress resistance. The results of this study were consistent with the previous studies [4], [10], [11], [19]. They found 20 minutes of light pressure of hand massage, a 30-minute session of TTM on to the back muscles, 80 minutes of touch massage (stroking) of the hands and feet, and a 5-minute hand holding could increase parasympathetic activity and decrease sympathetic activity, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Many previous studies found that massage could increase skin temperature and blood flow [1]- [3], decrease anxiety [4]- [7], depression [7] and pain, improve sleep quality [5], [8], increase renal blood flow [9], decrease sympathetic nervous activity and increase parasympathetic activity [10]- [11] and weight gain in infant [12] and decrease cortisol levels [10], [13], and stress [14]- [15].…”
Section: Introductionmentioning
confidence: 99%
“…42,43 The possible mechanism might be that Chinese hand massage improves the parasympathetic nerve activity and reduces the sympathetic nervous activity and decreases the secretion of epinephrine and norepinephrine. 44,45 The results of this trial also showed the anxiety symptoms at post-angiography were significantly lower than pre-angiography regardless of the Chinese hand massage group or control group, probably reason related to spontaneous decrease of anxiety with completing of angiography. For the secondary outcomes, no significant changes were observed on BP, heart rate, and SF-36 after Chinese hand massage, probably due to the short intervention duration (only 3 days) in this study.…”
Section: Discussionmentioning
confidence: 66%
“…Although this measure is used primarily for diagnostic classification purposes, recent studies suggest modulations of pNN50 by a different relaxation treatment. 38 The results of this study-in particular regarding the induction of relaxation by listening to MC sounds-can indicate a state of relaxation in the psychological and physiological activities like other similar relaxation states. On the basis of the increase in LF power, HF power, LF:HF ratio, and pNN50, the state of relaxation caused by listening to MC sounds is not exactly comparable with other states of meditation, anesthesia, or relaxation, even though there is some similarity.…”
Section: Discussionmentioning
confidence: 69%